Development of a Cub Scout Module Based on General Proficiency Requirements to Improve Elementary School Students' Learning Outcomes (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2025)
This study aims to develop a Cub Scout module based on General Proficiency Requirements (Syarat Kecakapan Umum/SKU) that is effective in improving the learning outcomes of elementary school students in the Cub Scout category. The module was developed using the PLOMP model, which consists of five stages: preliminary investigation, design, construction, evaluation and revision, and implementation. However, the implementation stage was not carried out, as the research focused solely on product development. The study was conducted at SDN Baros 04 Brebes with a sample of 20 Cub Scout students. The instruments used included expert validation sheets, observation sheets, questionnaires, and learning outcome tests. Data analysis was performed using quantitative descriptive methods and paired-sample t-tests. The module was deemed highly valid based on expert assessments, with an average score of 4.7. The average pretest score of 60.5 increased to 70.3 in the post-test, with an N-Gain score of 0.46, categorized as moderate. The paired-sample t-test showed a significant difference between pretest and post-test results (mean = 9.600; Std. Deviation = 5.720; Std. Error Mean = 1.280; t = -7.21; p < 0.001), indicating that the use of the module had a positive impact on students' learning outcomes. Students responded very positively to the module, with an average score of 4.1 (categorized as very good). The Cub Scout module based on SKU was proven to be valid and effective in enhancing students’ understanding, motivation, and learning outcomes. Further development at the implementation stage is recommended to evaluate long-term impacts and expand its application to other educational levels and contexts.